Wicazo Sa Review (JSTOR)
Wicazo Sa Review is an interdisciplinary journal devoted to the mission of assisting Indigenous peoples of the Americas in taking possession of their own intellectual and creative pursuits. During the past two decades, American Indian Studies has emerged as a central arena in which Indigenous populations in the United States define the cultural, religious, legal, and historical parameters of scholarship and creativity essential to the ongoing process of decolonization and to survival in the modern world. Founded in 1985, Wicazo Sa Review is a journal in support of this particular type of scholarship, providing inquiries into the Indian past and its relationship to the vital present.
Keywords: American Indian Studies